TRIASSIC STRATIGRAPHY AND SEDIMENTARY EVOLUTION OF THE ANNAPURNA TETHYS HIMALAYA (MANANG AREA, CENTRAL NEPAL) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
After initial opening of Neotethys in the Permian, thermal subsidence and deepening continued in the Triassic. In the Scythian, three pelagic nodular carbonate intervals of Early Griesbachian to Early Dienerian, Early to mid-Smithian and latest Smithian to earliest Aegean age are interbedded with shelfal shales (Tamba Kurkur Formation). Ammonoid-and conodont-rich condensed carbonates were deposited on the outer shelf, with maximum depths around 150+200 m reached during transgressive stages. The Anisian to lowermost Norian shelfal succession mostly consists of marly limestones and marls (Mukut Formation). Thick calcareous siltstones rapidly accumulated in the Carnian, testifying to a new stage of tectonic extension affecting the Tethys Himalayan passive margin. The thick Tarap Formation of largely mid-Norian age points to strong continuing subsidence. Interbedded siltstones and subarkosic sandstones ("lower member") are locally overlain by coral-bearing patch reefs ("middle member"). Chamosite-bearing hybrid arenites deposited at transgressive stages characterize the "upper member". The Triassic succession is capped by subarkoses and quartzarenites, interbedded with dolomitic to bioclastic hybrid sandstones and silty limestones ("Quartzite Series"), in turn overlain by the Kioto Limestone.
Keywords: Tethys Himalaya; Triassic; Ammonoids; Conodonts; Brachiopods; Corals; Stratigraphy; Arenite petrography.